Optical coherence tomography significance in managing complex neurofibromatosis 2-related papilledema: Report of a case. Issue 1 (January 2021) - Maria Bacci, Giacomo; Giordano, Flavio; Sardi, Iacopo; Evans, Gareth; Pathmanaban, Omar; Fonte, Carla; Trabalzini, Franco; Nappini, Sergio; Mura, Regina; Caputo, Roberto
This case describes the strong utility of optical coherence tomography in multidisciplinary management of a complex case of type 2 neurofibromatosis.